2009
DOI: 10.1111/j.1502-3885.2008.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Lake sediments from Store Koldewey, Northeast Greenland, as archive of Late Pleistocene and Holocene climatic and environmental changes

Abstract: A 2.9 m long sedimentary record was studied from a small lake, here referred to as Duck Lake, located at 76°25′N, 18°45′W on Store Koldewey, an elongated island off the coast of Northeast Greenland. The sediments were investigated for their geophysical and biogeochemical characteristics, and for their fossil chironomid assemblages. Organic matter began to accumulate in the lake at 9.1 cal. kyr BP, which provides a minimum age for the deglaciation of the basin. Although the early to mid‐Holocene is known as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 64 publications
2
44
1
1
Order By: Relevance
“…Comparative radiocarbon dating of aquatic mosses and terrestrial plants from one horizon revealed that the aquatic mosses were 520 years older than the terrestrial plant remains (Table 1; Klug et al 2009). Because terrestrial plant remains are regarded as representing the more reliable dates, 520 years was subtracted from all moss ages (Table 1; Klug et al 2009). For the Hjort Lake record, seven samples of terrestrial plant remains and four samples of aquatic mosses were dated (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative radiocarbon dating of aquatic mosses and terrestrial plants from one horizon revealed that the aquatic mosses were 520 years older than the terrestrial plant remains (Table 1; Klug et al 2009). Because terrestrial plant remains are regarded as representing the more reliable dates, 520 years was subtracted from all moss ages (Table 1; Klug et al 2009). For the Hjort Lake record, seven samples of terrestrial plant remains and four samples of aquatic mosses were dated (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The age models for Duck Lake and Hjort Lake (Fig. 2) are discussed in more detail in Klug et al (2009) and Wagner et al (2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Klug et al . ; Bennike & Wagner ). Therefore, the ages are apparently too old with respect to the lithological position in the sediment sequence.…”
Section: Resultsmentioning
confidence: 99%
“…; Klug et al . , b; Schmidt et al . ), the record from Lille Sneha Sø does not indicate a distinct Medieval warm period, but the Little Ice Age with its culmination c .…”
Section: Resultsmentioning
confidence: 99%